If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 295 = 11x + -5 Reorder the terms: 295 + x = 11x + -5 Reorder the terms: 295 + x = -5 + 11x Solving 295 + x = -5 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 295 + x + -11x = -5 + 11x + -11x Combine like terms: x + -11x = -10x 295 + -10x = -5 + 11x + -11x Combine like terms: 11x + -11x = 0 295 + -10x = -5 + 0 295 + -10x = -5 Add '-295' to each side of the equation. 295 + -295 + -10x = -5 + -295 Combine like terms: 295 + -295 = 0 0 + -10x = -5 + -295 -10x = -5 + -295 Combine like terms: -5 + -295 = -300 -10x = -300 Divide each side by '-10'. x = 30 Simplifying x = 30
| =8(2-3x)+8x | | 3x+4-4x-10= | | 6a-4=8a+2 | | 26=3x-1 | | z/7=5-18 | | 5(y+1)+y=6y+5 | | =5-2(2x+3) | | 12x+3-3x=117 | | s=30+3s | | J+4=-8 | | s=0+3d | | =-3+8(x+2) | | 662-18x-60=0 | | 1000=0 | | Y=x^3+2x^2-5x+10 | | (2x+1)2=64 | | =7+6x+9x+9 | | 16=2(x+13) | | 5-18=z/7 | | =1-8x-5x | | 5/6-2/4= | | 66-4x=5x+23 | | =4x+5(3x-3) | | 5x+14=59 | | 8x+13= | | 0=5s-(100+2s) | | 12-8x=5x+23 | | =-(1-5n)-7n | | 3(2x+1)=4x+17 | | 3s-8s=30 | | 13-5x+2x=10x | | 29=6+t |